Theoretical investigation of electrocatalytic activity of Pt-free dual atom-doped graphene for O2 reduction in an alkaline solution - Tahereh Jangjooye Shaldehi; Soosan Rowshanzamir (Scientific Reports)
Abstract Non-precious electrocatalysts as the alternative to Pt have become a hot research area in the last decade due to the suitable catalytic activity in Oxygen reduction reaction (ORR) in electrochemical systems. In this work, the density functional theory calculations were investigated to explore the activity of Fe, Cu, and Fe-Cu atoms supported by N-doped graphene as the ORR electrocatalyst for Oxygen-depolarized cathodes (ODCs). To this end, the ORR mechanism was surveyed in detail in the gas and solvent phases. The results show that the solvent phase leads to a higher overpotential and thermodynamic limiting potential. According to the density of states curves, there are strong interactions between metal atom and substrate that can effectively tune the electronics of catalysts. Bader's analysis confirms that, in addition to the single metal atoms, nitrogen atoms have also played a critical role in charge transfer between substrates and oxygen molecules in ORR. It is also predicted that Fe-Cu@NC SAC exhibits the highest catalytic activity which is consistent with thermodynamic limiting potential and theoretical overpotential of  − 0.26 and  0.66 (V vs. SHE), respectively, indicating that this type of catalyst may be a suitable candidate instead of precious metals in oxygen-depolarized cathodes in electrochemical devices.